THE INFLUENCE OF CUSTOMER INTIMACY ON RELIGIOUS BASED BRAND TRUST, CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN ISLAMIC BANKS - Yani Dahliani, Istifadah, Ika Barokah Suryaningsih, Deasy Wilandari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to examine the influence of Customer Intimacy on Religious Based Brand Trust, Customer Satisfaction, and Customer Loyalty in Islamic Banks. This research was conducted on 140 customers of Danamon Sharia bank in the Jember Regional Coordinating Board. The data used in this study are primary data and secondary data. This study indicates that customer intimacy has a significant effect on religious-based brand trust, customer satisfaction, and customer loyalty. This study also found that religious-based brand trust affects customer loyalty and customer satisfaction has an effect on customer loyalty. This study also suggests that future studies examine other variables related to the variables that have been used in this study.